Cultivating critical consciousness through digital video inquiry. Issue 4 (2nd October 2021) - Doerr-Stevens, Candance; Gibson, Melissa Leigh
ABSTRACT: As political participation across the globe grows increasingly contentious and accusations of "fake news" and "post-truth" politics rise, the how, where, and why of civic learning in schools are called into question. In contrast, multimodal practices such as digital video production continue to promote youth engagement and deliberation of social issues through dialogue, crowd-sourcing, and relationships. Herein we examine the classroom-based approaches to digital video inquiry as a problem-posing antidote to traditional banking approaches to civic education. To forward this claim, we describe 2 classroom uses of digital video production for critical social inquiry. In both cases, digital video inquiry invited students to move beyond banked knowledge about issues into a critical relationship with their topics of study and the communities affected — becoming a path of political participation not easily allowed in other pedagogical and social spaces.